Can Clinical Measures of Postoperative Binocular Function Predict the Long-Term Stability of Postoperative Alignment in Intermittent Exotropia?. (21st July 2020) - Wu, Yidong; Xu, Meiping; Zhang, Junxiao; Zhou, Jinjing; Wan, Minghui; Dai, Zhiyue; Peng, Tingting; Min, Seung Hyun; Hou, Fang; Zhou, Jiawei; Yu, Xinping
Abstract : Purpose . To evaluate whether clinical measures of postoperative binocular functions could predict the long-term stability of postoperative ocular alignment in children with intermittent exotropia. Methods . A retrospective study was performed in thirty-nine children (median: 7 years) who have been surgically treated from intermittent exotropia without overcorrection (less than 10 prism diopters [pd] of exodeviation at 1 month postoperatively). Angles of deviation and binocular functions were measured preoperatively and at 1 month, 6 months, and the final follow-up visit (≥24 months) postoperatively. We examined the relationships between postoperative drift (change of ocular alignment) and binocular functions (sensory fusion, fusional convergence amplitude, and stereoacuity). Results . The surgical success rate (esophoria/tropia ≤5 pd to exophoria/tropia ≤10 pd) dropped to 76.9% at 6 months after surgery and to 53.8% at individuals' last visit (mean: 37 months). The mean exodrift was 7.7 ± 9.2 pd from the postoperative month 1 to the final visit (p < 0.001 ) on distance fixation. Distance stereoacuity, central fusion, and fusional convergence amplitude significantly improved following surgery (p < 0.05 ). However, no significant correlation was found between their binocular functions measured at the beginning of each follow-up period and the postoperative drift (all p > 0.13 ). Conclusion . Our findings suggest that the clinical measures of sensory fusion, fusional convergence amplitude, and stereoacuity cannot serve as a robust predictor for the long-term stability of postoperative ocular alignment in patients who underwent successful surgery without overcorrection at 1 month postoperatively.